Enhancement of System Security by Using LSB and RSA Algorithms - Hummady, Muna M.; Hussein Morad, Ameer (Al-Khwarizmi Engineering Journal, 2022)
A steganography hides information within other information, such as file, message, picture, or video. A cryptography is the science of converting the information from a readable form to an unreadable form for unauthorized person. The main problem in the stenographic system is embedding in cover-data without providing information that would facilitate its removal. In this research, a method for embedding data into images is suggested which employs least significant bit Steganography (LSB) and ciphering (RSA algorithm) to protect the data. System security will be enhanced by this collaboration between steganography and cryptography.